Physical Education Attitude of Adolescent Students in the Philippines: Importance of Curriculum and Teacher Sex and Behaviors - Cruz, Angelita B.; Kim, Minsung; Kim, Hyun-Duck (Frontiers in Psychology, 2021)
The present study examined the attitudes of Filipino middle school students toward physical education and the associations between physical education attitude and various personal and external correlates of physical education. In total, 659 middle school students, aged between 12 and 19 years (M = 14.55; SD = 1.14), participated in the study. The Physical Education Attitude Scale (PEAS) was used to measure affective, cognitive, and motivational/behavioral attitudes of adolescent students toward physical education. Results showed that middle school students had moderate general attitudes toward PE. Female students had more favorable attitudes toward physical education when their teacher was male than female. When the teacher was female, male students were more satisfied with the physical education curriculum than female students. When the teacher was male, female students were more comfortable with the physical education curriculum than male students. Finally, students’ physical education attitude did not decrease as they got older, regardless of student sex. The findings provide a different perspective for the field and underscore the importance of not only the physical education curriculum but also the student–teacher relationship. To prevent the decline in students’ positive attitude toward and encourage positive behaviors toward physical education and activities, teachers should be very considerate about their interactions with students of the same sex; school administrators (e.g., principal and physical education department head), meanwhile, should focus at providing PE teachers with special training courses to enhance both their teaching and communication capabilities.